The Effects of Carbon Source and Growth Temperature on the Fatty Acid Profiles of Thermobifida fusca - Winkelman, Dirk C.; Nikolau, Basil J. (Frontiers in Molecular Biosciences, 2022)
The aerobic, thermophilic Actinobacterium, Thermobifida fusca has been proposed as an organism to be used for the efficient conversion of plant biomass to fatty acid-derived precursors of biofuels or biorenewable chemicals. Despite the potential of T. fusca to catabolize plant biomass, there is remarkably little data available concerning the natural ability of this organism to produce fatty acids. Therefore, we determined the fatty acids that T. fusca produces when it is grown on different carbon sources (i.e., glucose, cellobiose, cellulose and avicel) and at two different growth temperatures, namely at the optimal growth temperature of 50°C and at a suboptimal temperature of 37°C. These analyses establish that T. fusca produces a combination of linear and branched chain fatty acids (BCFAs), including iso-, anteiso-, and 10-methyl BCFAs that range between 14- and 18-carbons in length. Although different carbon sources and growth temperatures both quantitatively and qualitatively affect the fatty acid profiles produced by T. fusca, growth temperature is the greater modifier of these traits. Additionally, genome scanning enabled the identification of many of the fatty acid biosynthetic genes encoded by T. fusca.